Credit card usage behavior among working student - Che Aniza Che Wel; Nor Asiah Omar; Syed Shah Alam (Pusat Pembangunan Mahasiswa dan Perhubungan Alumni, Universiti Kebangsaan Malaysia, 2015)
This study seeks to examine the credit card usage behavior among working students. Research questionnaires were distributed among young working adults who are pursuing their Bachelor Degree in the executive mode at Universiti Kebangsaan Malaysia (UKM). T-test showed there is no significant different between male and female in terms of credit card usage. However, ANOVA analysis showed that there are significant different in credit card usage behavior among respondent within different gross monthly income.